Consumer behaviour in Gacha games - Ng, Jazlynn Liting (Nanyang Technological University, 2023)
Consumer behaviour in Gacha games has been the subject of many debates, with some arguing that it is a form of gambling. The potential gambling elements of Gacha games have attracted regulatory scrutiny in some countries, with some governments and consumer protection organizations calling for stricter regulations. This paper examine consumer behaviour in Gacha games and determine whether it is considered gambling by providing a comprehensive understanding of how the Gacha mechanism in Genshin Impact affects player engagement and spending habits.